Library Analytical Activity as a Means of Identifying, Verifying and Positioning Strategic Communications of the National Economy - Kulytskyi Sergii (Наукові праці Національної бібліотеки України імені В.І. Вернадського, 2019)

(untitled)
Strategic communications are considered as a component of the information support of the national economy functioning. Therefore, the analytical work of the scientific library is a means of identifying, verifying and positioning strategic communications of economic objects. The methodical approach for carrying out of these procedures and analysis of strategic communications in the economy is offered. The empirical basis of the research is the work performed in the National Library of Ukraine V. Vernadsky. An attempt is made to identify, verify and position strategic communications in Ukraine’s foreign trade. In the study of strategic communications of Ukrainian foreign trade, the analysis of statistical information was combined with the content analysis of media messages. It has been established that the destruction of economic myths about the exclusive role of ties with the Russian economy for the development of the Ukrainian economy significantly weakens Russia’s informational and psychological influence on the behavior of the subjects of the Ukrainian economy in Russian hybrid aggression.